Antiviral benzofurans from Eupatorium chinense. (February 2016) - Wang, Wen-Jing; Wang, Lei; Liu, Zhong; Jiang, Ren-Wang; Liu, Zhi-Wen; Li, Man-Mei; Zhang, Qing-Wen; Dai, Yi; Li, Yao-Lan; Zhang, Xiao-Qi; Ye, Wen-Cai
Graphical abstract: Eleven benzofuran dimers including five pairs of enantiomers (e.g. compounds2 and3 ), and a benzofuran trimer were isolated from the roots of Eupatorium chinense . The absolute configurations of the enantiomeric benzofuran dimers were determined on the basis of circular dichroism experiments and quantum chemical CD calculation method. Euparin showed potential antiviral effect against RSV LONG and A2 strains. Highlights: Twelve benzofurans were isolated from the roots of Eupatorium chinense . Five pairs of enantiomeric benzofuran dimers were separated by chiral HPLC. Euparin showed potential antiviral effect against RSV LONG and A2 strains. Abstract: Eleven benzofuran dimers, (+)-dieupachinins A–E, (−)-dieupachinins A–E and dieupachinin F, a benzofuran trimer trieupachinin A, as well as seven known compounds were isolated from the roots of Eupatorium chinense . The enantiomers of racemates dieupachinins A–E were separated by chiral HPLC. The structures with absolute configurations were elucidated on the basis of spectroscopic data, X-ray diffraction analysis, and circular dichroism experiments. The isolated compounds were evaluated for their in vitro antiviral activities against respiratory syncytial virus (RSV).